The Effect of Provincial Governance and Public Administration Performance Index on Total Factor Productivity in Vietnam - Anh Tung Tran; Phuong Anh Nguyen (Cogent Social Sciences)
Provincial governance is an essential aspect of public administration because it directly affects service delivery and the overall development of a region. In Vietnam, the provincial governance and public administration performance index (PAPI) is a tool used to measure the effectiveness of governance and public administration at the provincial level. This study investigates the relationship between PAPI indicators and Total Factor Productivity (TFP) at the provincial level in Vietnam from 2018 to 2022. According to the World Bank, productivity is the key to economic growth and development. This study calculates TFP at the provincial level using capital and labor as inputs and gross regional domestic product as the output. Then, the relationship between PAPI indicators and TFP is examined using a robust panel regression. The findings indicate that, on the one hand, corruption control, public services, environment management and e-governance have a beneficial impact on TFP at the provincial level. However, people’s participation, transparency, vertical accountability, and public administrative procedures, in certain ways, have a detrimental impact on TFP. These results provide further insight into Vietnamese residents’ perceptions of public administration. This research will also contribute to helping local government organizations identify the essential elements for improving public administration effectiveness.